3(x + 2) - 2(x - 1) = 7 x =?
Answers
Answered by
2
Answer:
here is your answer friend
Attachments:
![](https://hi-static.z-dn.net/files/d32/6d532a78ac14e2a7055864e37eaac0c2.jpg)
mayaakul169:
you do not no how to write friend
Answered by
1
Answer:
The answer is x=4/3
Step-by-step explanation:
3(x+2) - 2(x-1) = 7x
3x + 6 - 2x + 2 = 7x
x + 8 = 7x
8 = 6x
x = 8/6
x = 4/3
Hope it helps yo^_^
Similar questions
Science,
3 months ago
Psychology,
3 months ago
Math,
6 months ago
Physics,
6 months ago
Biology,
1 year ago